2016
DOI: 10.1016/j.compstruc.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Large displacement analysis of sandwich plates and shells with symmetric/asymmetric lamination

Abstract: This paper proposes a kinematic model for sandwich plates and shells, utilising a novel zigzag function that is effective for symmetric and asymmetric cross-sections, and employing a piecewise through-thickness distribution of the transverse shear strain. The proposed model is extended to large displacement analysis using a co-rotational framework, where a 2D local shell system is proposed for the direct coupling of additional zigzag parameters. A 9-noded co-rotational shell element is developed based on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This is another EICR algorithm for shell element frame, which was firstly introduced by Izzuddin, 22 and the pertaining applications for many different shell element studies can be found in the literature. [23][24][25][26][27][28] Different from the former 2 EICR formulations, it does not extract pure deformation from total deformation completely. Similar to the classical co-rotational method presented in Section 3.1, this algorithm starts from the establishment of the relationship between local and global variables, but the interesting thing is that the local deformation in this formulation is not pure.…”
Section: Co-rotational Methods Without Removing Rigid Body Movement Comentioning
confidence: 99%
See 1 more Smart Citation
“…This is another EICR algorithm for shell element frame, which was firstly introduced by Izzuddin, 22 and the pertaining applications for many different shell element studies can be found in the literature. [23][24][25][26][27][28] Different from the former 2 EICR formulations, it does not extract pure deformation from total deformation completely. Similar to the classical co-rotational method presented in Section 3.1, this algorithm starts from the establishment of the relationship between local and global variables, but the interesting thing is that the local deformation in this formulation is not pure.…”
Section: Co-rotational Methods Without Removing Rigid Body Movement Comentioning
confidence: 99%
“…This is another EICR algorithm for shell element frame, which was firstly introduced by Izzuddin, and the pertaining applications for many different shell element studies can be found in the literature . Different from the former 2 EICR formulations, it does not extract pure deformation from total deformation completely.…”
Section: Existing Co‐rotational Algorithmsmentioning
confidence: 99%
“…Simplified FE models can overcome these restrictions, where common methods with improved efficiency rely on the employment of sandwich shell finite elements, using layerwise laminate theory (Carrera 1998), while still defining distinct material properties for the faceplates and the homogeneous core. An effective approach has previously been proposed by Liang and Izzuddin (2016) to perform linear and nonlinear analysis of sandwich structures using a 2D local shell system, where a co-rotational approach is employed to model geometric nonlinearity (Izzuddin 2007;Izzuddin and Liang 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These solutions are significantly related to application of composite materials [1][2][3][4][5][6]. One of important areas in shell-type structures (bodies of missiles, ships, fuselages and wings of aircraft and helicopters, as well as other items) is creation and expanding application of multilayer [7][8][9][10][11][12], sandwich structures the elements of which consist of two carrying layers and the light core between them [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%